Estudo da retina peripapilar e do disco óptico em pacientes com alta miopia por meio da Tomografia Óptica de Domínio Espectral - Jorge, Felipe Abdo [UNIFESP] (2017)
PURPOSE: To analyze the relationship between high myopia and alterations in retinal nerve fiber layer (RNFL) using Spectral Domain Optical Coherence Tomography (SD-OCT). METHODS: Patients >18 years of age with high myopia (defined as axial length (AL) ≥ 26mm and/or spherical equivalent ≤ -8D) were included. Exclusion criteria were: optic neuritis, history of any other neuro-ophthalmic disease, glaucoma, retinal diseases, history of vitreous-retinal surgery or previous uveitis. All subjects underwent comprehensive ophtalmic examination, axial length biometry (IOL Master, Carl Zeiss Meditec, Dublin, CA) and peripapillary RNFL thickness measurement (Spectralis OCT, Heidelberg Engineering, Germany). Linear regression analysis and Spearman’s rank correlation test were used. Data were corrected for correlation between eyes. RESULTS: A total of 29 eyes of 15 individuals were evaluated. The mean (standard deviation [SD]) age was 30.2 (6.4) years, 4 (27%) individuals were male and 11 (73%) were female. RNFL thickness was correlated with both spherical equivalent and axial length in all sectors, except temporal. RNFL thickness decreased 6.5 μm for each 1 mm of axial length increase (P<0.001). RNFL thickness increased 2.5 μm for each 1 diopter of spherical equivalent increase (P<0.001). CONCLUSION: RNFL thickness is correlated with axial length and spherical equivalent in high myopia.